An evaluation of 2.0 McFarland Etest method for detection of heterogeneous vancomycin-intermediate Staphylococcus aureus - Montri Pongkumpai (2018)
Background: Staphylococcus aureus with reduced susceptibility to vancomycin or heterogeneous vancomycinintermediate S. aureus (hVISA) have become increasingly reported from various parts of the world. hVISA cannot be detected by routine test for minimal inhibitory concentration (MIC) for vancomycin. The gold standard method for detection, population analysis profiles (PAP) method, is complicated, time-consuming, expensive, and needs well-trained microbiologists. Objective: Evaluate of 2.0 McFarland Etest method, in comparison with the PAP method, for detection of hVISA in clinical specimens. Methods: All methicillin-resistant S. aureus strains from clinical specimens isolated from consecutive patients attended at King Chulalongkorn Memorial Hospital and Siriraj Hospital, Bangkok between 2006 and 2007 were studied. 1 hundred nineteen specimens were obtained. The PAP method detected six hVISA strains 5 from blood and from cultures) from four patients at King Chulalongkorn Memorial Hospital, accounting for a prevalence of 6.35%. The MIC determined by agar dilution method was in the range of 2-3 ìg/mL. Results: 2.0 McFarland Etest method detected no false positive and five false negatives (42%), and gave a sensitivity and a specificity of 16.7% and 100%, respectively. The one-point population analysis screening method detected two false positives and 1 false negative, and gave a sensitivity of 83.3% and a specificity and 98.2%. Conclusion: The 2.0 McFarland Etest method had a very good specificity but a poor sensitivity for detecting hVISA. It may be used as an alternative method to confirm detection of hVISA.